Proceedings of the 2019 1st International Conference on Engineering and Management in Industrial System (ICOEMIS 2019) 2019
DOI: 10.2991/icoemis-19.2019.57
|View full text |Cite
|
Sign up to set email alerts
|

Application of Grey Teory Method for Halal Food Risk Assessment Based on the Traceability System in Food Supply Chain

Abstract: The purpose of this study was to assess the risk of based halal food. The method that will be used in conducting a risk assessment using the Grey Theory method. There are three risks that need to be considered for fish meatball SME, namely the risk of adding preservative supporting ingredients to meatballs, the risk of contamination with lizard dung, rats, cockroaches. Supporting materials used are not in accordance with the list of ingredients in LPPOM MUI. Therefore fish meatball SME can communicate risk by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Hernadewita and Saleh (2020) conducted a systematic analysis of 35 construction supply chain risk identification and assessment frameworks, and found that the combination of supply chain operation reference model (SCOR) and failure mode and effect analysis (FMEA) is an effective method to identify and evaluate construction supply chain risk [12]. Handayani and Prihatiningsih (2019) take small and medium-sized enterprises that produce fish balls as the research subject, identify the production risk factors based on the traceability system, and use the gray theory method to evaluate the impact of hazardous substances in halal food [13]. Zhang et al (2018) used structural equation modeling to explore the transmission of supplier's disruption risk along the supply network in Chinese automotive-related companies, and revealed that the disruption risk affects its manufacturers, who conduct direct business trades with it [14].…”
Section: Research On the Risk Assessment Of The Supply Chain Transmis...mentioning
confidence: 99%
“…Hernadewita and Saleh (2020) conducted a systematic analysis of 35 construction supply chain risk identification and assessment frameworks, and found that the combination of supply chain operation reference model (SCOR) and failure mode and effect analysis (FMEA) is an effective method to identify and evaluate construction supply chain risk [12]. Handayani and Prihatiningsih (2019) take small and medium-sized enterprises that produce fish balls as the research subject, identify the production risk factors based on the traceability system, and use the gray theory method to evaluate the impact of hazardous substances in halal food [13]. Zhang et al (2018) used structural equation modeling to explore the transmission of supplier's disruption risk along the supply network in Chinese automotive-related companies, and revealed that the disruption risk affects its manufacturers, who conduct direct business trades with it [14].…”
Section: Research On the Risk Assessment Of The Supply Chain Transmis...mentioning
confidence: 99%
“…No use, distribution or reproduction is permitted which does not comply with these terms. [12] Halal treaceability system…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%